Effects of sugar type and regional variation on the biochemical composition of royal jelly (Apis mellifera L.) - Karlidag, Semiramis; Basgel, Serkan; Maras, Zeynep; Uyumlu, Ayse Burcin; Demir, Nurullah; Ugur, Yilmaz; Erdogan, Selim (Nature Portfolio, 2025)
Royal jelly, owing to its rich biochemical composition, is widely used in apitherapy and human nutrition. To enhance its production, honeybee colonies are often supplemented with industrial carbohydrate sources. This study aimed to investigate how different locations (Do & gbreve;an & scedil;ehir and Uluk & ouml;y) and carbohydrate types influence the biochemical composition of royal jelly, including sugar content, enzymatic activity, and phenolic compounds. The results revealed that both location and carbohydrate source significantly affected the biochemical profile of the samples. The Do & gbreve;an & scedil;ehir-glucose-fed group exhibited the highest 10-hydroxy-trans-2-decenoic acid (10-HAD) content (2.77%, w/w; p < 0.001), whereas the Do & gbreve;an & scedil;ehir-control group had the lowest (1.41%, w/w; p < 0.001). Environmental conditions in Do & gbreve;an & scedil;ehir appeared to promote 10-HDA production, and glucose feeding proved to be an effective strategy for optimizing it. Although glucose, fructose, and sucrose levels were similar between locations, maltose content differed significantly. The highest glucose ratios were detected in the Do & gbreve;an & scedil;ehir bee-feed group (3.82%) and the Uluk & ouml;y bee-feed group (3.57%). Invertase activity (4.51 +/- 1.34 U/mL) and catalase activity (21.78 +/- 0.80 U/mL) were highest in glucose-fed bees, whereas these parameters were lowest in the sucrose-fed group (0.72 +/- 0.16 and 11.25 +/- 2.66 U/mL, respectively; p < 0.01). Glucose feeding markedly increased the levels of invertase, catalase, total protein, amino acids, proline, and 10-HDA in royal jelly (p < 0.01). In conclusion, both environmental factors and carbohydrate-based feeding exert significant effects on the biochemical composition of royal jelly.
Keywords: Carbohydrate feeding; Royal jelly; Sugar; Catalase; 10-HDA; Phenolic compounds